2018
DOI: 10.1016/j.antiviral.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput drug screening using the Ebola virus transcription- and replication-competent virus-like particle system

Abstract: The massive epidemic of Ebola virus disease (EVD) in West Africa, followed in recent months by two outbreaks in the Democratic Republic of the Congo, underline the importance of this severe disease. Because Ebola virus (EBOV) must be manipulated under biosafety level 4 (BSL4) containment, the discovery and development of virus-specific therapies have been hampered. Recently, a transient transfection-based transcription- and replication competent virus-like particle (trVLP) system was described, enabling modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The majority of these compounds have been used to treat psychotic disorders or allergic diseases by binding to G protein-coupled receptors (GPCRs). This finding was partially consistent with previous reports of GPCR modulators as anti-EBOV compounds (19)(20)(21). Particularly, sertindole (EC50, 0.7 M; SI, > 45.8), raloxifene hydrochloride (raloxifene; EC50, 0.5 M; SI, 47.1) and ibutamoren mesylate (ibutamoren; EC50, < 0.4 M; SI, > 81.1) showed the most prominent antiviral activity among the 15 major hit compounds.…”
Section: Evaluation Of Antiviral and Cytotoxic Effectssupporting
confidence: 90%
See 1 more Smart Citation
“…The majority of these compounds have been used to treat psychotic disorders or allergic diseases by binding to G protein-coupled receptors (GPCRs). This finding was partially consistent with previous reports of GPCR modulators as anti-EBOV compounds (19)(20)(21). Particularly, sertindole (EC50, 0.7 M; SI, > 45.8), raloxifene hydrochloride (raloxifene; EC50, 0.5 M; SI, 47.1) and ibutamoren mesylate (ibutamoren; EC50, < 0.4 M; SI, > 81.1) showed the most prominent antiviral activity among the 15 major hit compounds.…”
Section: Evaluation Of Antiviral and Cytotoxic Effectssupporting
confidence: 90%
“…Based on their target analysis, we found that GPCRs were closely linked to the EBOV life cycle. Using the same trVLP system, N. Lee et al found GPCR modulators as antiviral hits, suggesting experimental reliability (19). However, in contrast to the previous study, from a technical perspective, we adopted the dual luciferase assay to measure the antiviral activity and cytotoxicity simultaneously from the same sample, while the cytotoxicity was determined in an image-based manner via Hoechst staining.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lee and coworkers reported that the new antimalarial drug ferroquine inhibits EBOV entry, by affecting the pH dependent viral fusion step [77].…”
Section: Antiparasitic Drugsmentioning
confidence: 99%
“…Iminodyn 17 is an inhibitor of the GTPase activity of dynamins, a class of proteins involved in the scission of newly formed membrane vesicles, which can block EBOV entry. Nobiletin and ML9 were reported to affect the trafficking of viral particles by targeting the PI3K-Akt pathway and the miosyn light chain kinase activity, respectively [77].…”
Section: Miscellaneous Compounds That Inhibit Ebov Entrymentioning
confidence: 99%
See 1 more Smart Citation